Pengolahan Terbitan Resmi Pemerintah di Perpustakaan Dinas Pariwisata dan Ekonomi Kreatif Provinsi Sumatera Barat - Sari, Karina Fatmala; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
The purposes of this article are to describe:(1) processing of official government publications in the Library Department of Tourism and Creative Economy of West Sumatera Province; (2) obstacles in processing official publications in the Library of the Department of Tourism and Creative Economy of West Sumatera Province; (3) efforts should be made so that the processing of official government publication goes well in the Library of the Department of Tourism and Creative Economy of West Sumatera Province. Data were collected through direct observation and interviews with librarians Library Department of Tourism and Creative Economy of West Sumatra Province. Analyzing data descriptively. Based on analyzing the data, we can conclude the following matters. First, the processing of official government publications in the Library of the Department of Tourism and Creative Economy of West Sumatera Province has not been processed properly. Secondly, there are obstacles encountered in the processing of official government publications. Third, efforts to overcome these obstacles are the processing of official government publications in the Library of the Department of Tourism and Creative Economy of West Sumatera Province.Â Keywords: Government Publication